Approaches to measuring average and median wages in Russia and abroad: data sources and users - Xu, Yeqiang; Sarinova, Alfiya; Sarinova, Assiya Zh; Lozhnikova, Anna V. (Вестник Томского государственного университета. Экономика)
This article focuses on the measurement of average and median wages, which are closely related to indicators of living standards. We reveal the problem of insufficient discussion of current issues in labor income measurement in contemporary Russian economic literature. The aim of this article is to contribute to the scientific substantiation of the relationship between methodology, procedure, and algorithm in measuring the average and median wages of wage earners in the Russian Federation (RF). The novelty of this study lies in comparing primary indicators from the Russian Federal State Statistics Service (Rosstat) and foreign companies and formulating conclusions about significant differences between estimates from the United States, Europe, and Russia in the studied area. A comparative analysis of Rosstat’s (Russia) estimates of average and median wages shows an inverse relationship to those of US and European companies. To address the problems of significant discrepancies and unreliability of Russian figures, we propose streamlining the relationship between the concepts of “methodology,” “procedure,” and “algorithm” in measuring average and median wages in the RF. To this end, we propose meaningfully linking “methodology” with formulas for calculating average wages, “procedure” with the object of measurement, and “algorithm” with the source/subject of measurement and users of measurement results. We focus on the experiences of American and European companies as being very important, primarily in the context of users of these indicators, i.e., company employees. Informing wage earners about the results of average and median wage measurements could be an effective tool for overcoming labor income inequality in the RF.